A novel anthracene derivative with an asymmetric structure as an electron transport material for stable Rec. 2020 blue organic light-emitting diodes. Issue 3 (2nd July 2020) - Liu, Cheng; Zhang, Dongdong; Duan, Lian
ABSTRACT: The stability of blue organic light-emitting diodes (OLEDs) is highly restricted by both the low electron transport mobility and the stability of the electron transport materials (ETMs). Anthracene-derivative-type ETMs have been proven to be potential materials for solving the aforementioned problem, but their performance still needs to be improved. In this study, a novel anthracene derivative with an asymmetric structure was developed as an ETM in deep-blue devices, realizing a 10.41 cd/A current efficiency, a low driving voltage of 4.04 V, (0.139, 0.047) Rec. 2020 CIE coordinates, and a long T99 lifetime of over 100 h at the 20 mA/cm 2 current density. Single-crystal diffraction showed that ET-01 has a face-to-face π-π stack, which is the reason for its good performance. Notably, when the lithium quinolate (Liq) doping ratio was further tuned, one of the devices showed no obvious degradation after 140 h of continuous operation at 20 mA/cm 2, representing the champion data in the scientific literature.